Senderización y señalética para las Cascadas del Rio Pindo, de la Parroquia Rural Uzhcurrumi, Cantón Pasaje, Provincia de El Oro - Jaramillo Lima, Andrea Elizabeth (2016)
Tourism in Ecuador during the last six decades has undergone a continuous expansion and diversification, since it has a great variety of climates, microclimates, landscapes, which have turned tourism into one of the most important economic sectors of the world. Generator of resources for conserving great natural and cultural wealth, more than that, it shares with each one of its attractions. Tourism is focused as a sustainable development for the people who have achieved achievements in their economies which shows that the development of a country is through sustainable tourism. The tourism industry began to develop in the rural sector, achieving a constant dynamism, that is why these areas should be signposted and senderizados, since a good tourist signage is essential to provide tourists with adequate information and guidance. The present project has as main objective the proposal of SENDERIZATION AND SIGNALING FOR THE CASCADES OF RIO PINDO, OF THE RURAL PARISH UZHCURRUMI, AND OF THE CANTÓN PASSENGER PROVINCE OF EL ORO. The specific objectives were: to make a tourist diagnosis of the current situation of the rural parish Uzhcurrumi for which the following methodology was applied; We used the scientific method which helped us to base the study object, we applied an analytical and synthetic method, which allowed an analysis of the current situation of the place and allowed to totalize all the elements collected, we used the matrix of Carla Ricaurte Quijano Adapted to the current reality of the place, also applied the methodology for inventory of tourist attractions of MINTUR, through techniques such as direct observation and finally the technique of interviewing the main actors of the parish GAD was carried out to obtain accurate information of the sector To subsequently develop the SWOT analysis and strengthen the assessment of the diagnosis. For the fulfillment of the second specific objective proposed to propose the Senderización and Signaltics for the Rio Pindo Cascades of the rural Parish Uzhcurrumi Cantón Pasaje Province of El Oro, the inductive and deductive method were used which are necessary to obtain general data and finally to obtain conclusions And recommendations. Subsequently, the carrying capacity was developed using the methodology of Miguel CIFUENTES, which established the maximum number of visitors that can receive the trail that leads to the attractions. During the field work the GPS was used to determine the UTM coordinates of the trail and points where the interpretive and informative signs were installed. Once the GPS 6 data were obtained, a base map was drawn up and the location coordinates were entered to obtain the tourist trail route. And to culminate with the third objective was formulated to develop an environmental impact study of the waterfalls of the Rio Pindo waterfalls of the Rural Parish Uzhcurrumi Cantón Pasaje province of El Oro, it was determined the possible environmental impacts that will generate the implementation of the project, through The Leopold Cause-Effect evaluation matrix. As for the results of the research, a diagnostic of the current situation of the rural Uzhcurrumi parish was carried out, in which it was possible to know general data about the population, such as flora, fauna, Basic services, governance, receiving community; All this information was reflected in the records of the Ministry of Tourism, as well as the collection of information based on the diagnostic methodology of the Matrix Carla Ricaurte, in addition to this it was necessary to conduct the interviews with the main actors of the parochial GAD , This helped to reinforce the information, it was also considered a design of signage with relevant information of the attractions to visit taking as a reference the Manual of Tourist Signage, elaborated by the Ministry of Tourism; And, based on the information obtained, geo-referenced maps of the Senderization and Signaling of the trail were drawn; Which according to calculations of the Load Capacity can receive 49 people approximately per day. Finally, the respective pictograms of tourist activities, pictograms of tourist attractions of approximation signs and destination fences for the trail were designed, which add up to a total of 12 signs, attaching to them the investment budget in case of implementing the proposal. As a conclusion we have that the parish Uzhcurrumi has a great variety of important tourist attractions, to boost tourism development the same that need to be adequate and enhanced by the relevant authorities, it should be emphasized that each site lacks signs that allow tourists to guide themselves correctly, And therefore the proposal of senderizacion and signage will contribute positively to the attraction and its visitors when visiting the attraction. Among the most important recommendations it is recommended to the parish GAD Uzhcurrumi work together with agreements with the MINTUR wi.th projects that are related tourist, as tourist signage, improve the infrastructure participatory workshops, updating of tourist attractions among others with the objective of attracting great demand of tourists Local, national and international.